Study of white frangipani flower and bitter grape stem ethanol extract combination on antibacterial and antioxidant activities - KRISHNA PURNAWAN CANDRA; WIJAYANTI KUSUMA WARDHANI; ANTON RAHMADI; MIFTAKHUR ROHMAH; YULIANI YULIANI (Jurnal Natural, 2020)
Frangipani flower (Plumeria acuminata) and bitter grape (Tinospora crispa L. Miers) stem extract alone shows antimicrobial and antioxidant activities. However, there is a limited report about the actions from the combination of both extracts. Combinations of ethanol extract of white frangipani flower (EFF) and ethanol extract of the bitter grape stem (EBS), each of 0, 1, 2, and 3% were tested for inhibition against Staphylococcus aureus growth and DPPH (1,1-diphenyl,2-picrylhydrazyl) free radicals. A yield of 3.17 and 2.62 g of EFF and EBS, respectively, were resulted from 100 g of dried powdered of the white frangipani flower and bitter grape stem using 200 mL of absolute ethanol. The antimicrobial test was assayed using a 10% stock solution of extract diluted in water. The combination of EFF and EBS showed a synergistic effect on antimicrobial activity, but it proved an antagonistic effect on antioxidant activity. The combination of EFF 3% and EBS 3% showed the highest inhibition index on the S. aureus growth , i.e. 2.02±0.06, which is higher than the inhibition index of Amoxycillin 2%, i.e. 1.85±0.09. The highest antioxidant activity showed by 1% EFF alone (57.5 ± 0.60%), while the lowest was from the combination of EFF 1% and EBS 3% (23.4±0.30%).